Avaliação do diafragma piezelétrico de baixo custo no monitoramento do processo de retificação plana tangencial - Fabiano, Luiz Felipe Gilli [UNESP]; Ribeiro, Danilo Marcus Santos [UNESP]; Junior, Pedro Oliveira Conceição [UNESP]; da Silva, Kauê Luís Oliveira [UNESP]; de Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (My University, 2017)
The machining processes are of extreme importance for the manufacture of mechanical parts, the parts demand high dimensional and geometric precision and quality in its construction. Among the machining processes, the grinding process stands out as one of the most used processes, due to its precision and good finish. It is essential that this process is well known, since it is in the last stage of manufacture. Thus, problems during the grinding process compromise the part and can be lost the work carried out in all previous stages, resulting in high cost in production and loss of raw material. The objective of this work is to develop a method of monitoring the surface conditions of the parts by performing a comparative study of the roughness and burning of rectified parts with the signals captured by a low cost piezeletric diaphragm composed of Lead Titanium Zirconate (LTZ), as well as an acoustic emission sensor (AE). The experimental tests were per-formed on a flat tangential grinding machine, where a test bench was developed using a CBN grinding wheel with resinoid binder in VC131 steel test bodies. Later, to characterize the surface of the pieces, visual inspection, roughness measurements, Vickers micro hardness measurements and a metallographic analysis were performed to verify the microstructure of each piece. The signals were acquired through an oscilloscope of high sampling rate and later treated with digital filters. These signals were then compared to the firing and roughness of each part under their respective conditions, through signal processing techniques. It was noticed that the increase of the roughness, as well as the occurrence of the burning of the piece, has a relationship with increase of the RMS signal of the PZT and the EA. By means of this study, the efficiency of the signal emitted by the low cost piezoelectric diaphragm was verified, which presented a satisfactory correspondence with the condition of the parts of the steel VC 131 after the grinding, according to the spectral analysis and the study of the signal in proper frequency bands.
Low-cost piezoelectric diaphragm evaluation in the monitoring of the flat tangential grinding process
Keywords: Acoustic emission; Grinding; Monitoring; Piezoelectric patch